2011
DOI: 10.1016/j.neuron.2011.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis Promotes Rapid Dopaminergic Signaling

Abstract: SUMMARY D1 dopamine receptors are primary mediators of dopaminergic signaling in the CNS. These receptors internalize rapidly following agonist-induced activation but the functional significance of this process is unknown. We investigated D1 receptor endocytosis and signaling in HEK 293 cells and cultured striatal neurons using real-time fluorescence imaging and cAMP biosensor technology. Agonist-induced activation of D1 receptors promoted endocytosis of receptors with a time course overlapping that of acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 59 publications
8
151
0
1
Order By: Relevance
“…Retromer co-localized with V2R after internalization and formed a complex with it; titrating retromer expression by transgene overexpression or by siRNA knockdown showed that retromer has an antagonistic effect on cAMP generation by V2R. Together with recent work on ␤-arrestins and the PTHR (6,9,10,53), this work supports a new noncanonical model of GPCR signaling, wherein ␤-arrestins augment rather than attenuate hormone actions and in which desensitization is instead mediated by the retromer sorting complex on early endosomes.…”
Section: Discussionsupporting
confidence: 64%
“…Retromer co-localized with V2R after internalization and formed a complex with it; titrating retromer expression by transgene overexpression or by siRNA knockdown showed that retromer has an antagonistic effect on cAMP generation by V2R. Together with recent work on ␤-arrestins and the PTHR (6,9,10,53), this work supports a new noncanonical model of GPCR signaling, wherein ␤-arrestins augment rather than attenuate hormone actions and in which desensitization is instead mediated by the retromer sorting complex on early endosomes.…”
Section: Discussionsupporting
confidence: 64%
“…Sustained cAMP and G S signaling by receptor internalization in early endosomes was originally reported in 2009 for two distinct GPCRs, the thyroid-stimulating hormone receptor (TSHR) (35) and PTHR (2), and recently expanded to the dopamine D1 receptor (D1R) (36). Endosomal G-protein signaling appears to be an alternative pathway not only for G S -but also for inhibitory G protein (Gi)-coupled receptors, as demonstrated for the sphingosine-1-phosphate receptor (37).…”
Section: Discussionmentioning
confidence: 98%
“…These specific downstream effects appear to include selective changes in gene expression, demonstrated for b-adrenergic receptors, and the control of thyroid hormone secretion in the case of the thyroid-stimulating hormone receptors (Calebiro et al, 2010;Tsvetanova et al, 2015). However, signaling from internal sites may also affect processes at the cell surface, as shown for dopamine D 1 -receptor-dependent neuronal excitability (Kotowski et al, 2011).…”
Section: Spatial Aspects-receptor Localization and Spatial Signalingmentioning
confidence: 99%